Risperidone and serum lipid profile changes in child and adolescent patients - Karaman, Mehmet Goksin; Ozdemir, Esra; Yurteri, Nihal; Erdogan, Ayten (Neurology, psychiatry, and brain research, 2011)
Atypical antipsychotics (AAPs) have been reported to cause metabolic dysregulation that can cause AAPs-related weight gain. The purpose of this study was to assess triglyceride, cholesterol, and weight changes among risperidone-treated children and youths. Eighty-one subjects treated with risperidone for any psychiatric disturbances were included in the study. Fasting total low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), total cholesterol (TC), and triglyceride (TG) levels were measured at the baseline and at the sixth month of treatment. TG, TC and LDL-C levels increased over time and reached statistical significance but there has been no change in HDL-C levels. Seven subjects (8.64%) crossed the threshold into clinically significant hypertriglyceridemia, four subjects (4.94%) crossed the threshold into clinically significant hypercholesterolemia, defined as going over the 95th percentile of published age normed plasma TG and TC levels, respectively. There was a positive correlation between TG and TC elevations and weight gain. There was no significant association with age, gender, diagnoses, risperidone dose and changes of serum TG, TC or LDL-C levels. The present study identified significant associations between lipid dysregulation and risperidone treatment. Since there is little research available on long-term lipid profile follow-up with atypical antipsychotics treatment in children and youths, controlled studies in larger samples should be carried out to reveal the relationship between risperidone use and plasma lipid parameters in the pediatric population.